Theoretical study of the inclusion processes of the phenylurea herbicide metobromuron in β-cyclodextrin. - Leila Nouar; Sakina Haiahem; Abdelaziz Bouhadiba; Fatiha Madi; Leila Largate; Fateh Djebloune (ANSInet, Asian Network for Scientific Information, 2011)
We investigated the inclusion process of phenylurea herbicide metobromuron (MB) in beta cyclodextrin (β-CD) with 1:1 stoichiometry using: (1) MM+ force field of molecular mechanics in order to research the lowest energy structure of the inclusion complex. (2) Superior levels of calculations were made such PM3, B3LYP/6-31G*, HF/6-31G* and ONIOM2 methods in order to approach the ideal geometry and provide further insight into the different complexation properties of the guest molecule. The data suggest that: The B orientation is significantly more favourable than the A orientation by an energy difference of 1.02 kcal mol-1 according to PM3 calculations. The geometry of the most stable complex shows that the aromatic ring is deeply self-included inside the hydrophobic cavity of β-CD also an intermolecular hydrogen bond is established between host and guest molecules. The formation of the inclusion complex is predicted to be an enthalpy-driven process in gas phase which is in accord with the experimental results. The statistical thermodynamic calculations by PM3 demonstrate that 1:1 MB/β-CD complex is favored by a negative enthalpy change.